Complications of laparoscopic cholecystectomy - Al-aubaidi, Tariq E. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: cholecystectomy is one of the most frequently performed operations. Open cholecystectomy has been the gold standard for over 100 years .laparoscopic cholecystectomy was introduced in 1980s. Patient and methods: Two hundred patients admitted to first surgical unit in Baghdad teaching hospital from first May 2007- first May 2009 with gall stone disease both symptomatic and asymptomatic, of both genders and any age were evaluated by history, examination and investigations and data was collected. Results: Two hundred patients underwent LC in the study period. 181(90.5%)were females and 19(9.5%)were males. The most common age group was between 21-40 years (55%), bleeding was the commonest complication, occurring from trocar site in 11(5.5%) cases, vascular injury in Calot’s triangle in 9(4.5%) cases and liver bed in 23(11.5%) cases. Spilled gall stones occurred in 32(16%) cases, biliary leak in 7(3.5%) cases including common bile duct injury in one case. Port site infection was seen in 11(5.5%). There was no bowel injury or port site hernia and there was no mortality. Conclusion: LC is a safe and effective procedure in almost all patients with cholelithiasis. Good training and dealing with the complications makes this procedure with good results and less complication.